2019
DOI: 10.1186/s13100-019-0158-3
|View full text |Cite
|
Sign up to set email alerts
|

Human transposons are an abundant supply of transcription factor binding sites and promoter activities in breast cancer cell lines

Abstract: Background Transposable elements (TE) are commonly regarded as “junk DNA” with no apparent regulatory roles in the human genome. However, a growing body of evidence demonstrates that some TEs exhibit regulatory activities in a range of biological pathways and diseases, with notable examples in bile metabolism and innate immunity. TEs are typically suppressed by epigenetic modifications in healthy somatic tissues, which prevents both undesirable effects of insertional mutagenesis, and also unwanted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 93 publications
(156 reference statements)
2
33
0
Order By: Relevance
“…Our analysis revealed that the L1PA2 transposons were significantly enriched in E2F1 and MYC binding sites in MCF7 cells. Furthermore, luciferase assays in triple negative breast cancer cells confirmed the activity of an L1PA2-derived promoter, where the transposon was found to account for a significant proportion of promoter activity to the SYT1 gene (Jiang and Upton 2019). In support of our findings, a recent paper by Jang et al showed that the L1PA2-derived promoter activity was not limited to SYT1, and was also seen for other oncogenes, such as MET, XCL1…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our analysis revealed that the L1PA2 transposons were significantly enriched in E2F1 and MYC binding sites in MCF7 cells. Furthermore, luciferase assays in triple negative breast cancer cells confirmed the activity of an L1PA2-derived promoter, where the transposon was found to account for a significant proportion of promoter activity to the SYT1 gene (Jiang and Upton 2019). In support of our findings, a recent paper by Jang et al showed that the L1PA2-derived promoter activity was not limited to SYT1, and was also seen for other oncogenes, such as MET, XCL1…”
Section: Introductionsupporting
confidence: 89%
“…We previously reported the regulatory activity of several transposon subfamilies in the context of breast cancer (Jiang and Upton 2019). Our analysis revealed that the L1PA2 transposons were significantly enriched in E2F1 and MYC binding sites in MCF7 cells.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…SINEs (e.g. Alu repeats) and other transposed sequences are known to serve as direct silencers of gene expression due to their repressed chromatin marks (histone H3 methylated at Lys 9) ( 69 , 70 ). Moreover, non-B DNA structures such as G4, cruciform, triplex and Z-DNA have been shown to silence expression of adjacent genes ( 65 , 71 , 80 , 7279 ).…”
Section: Discussionmentioning
confidence: 99%
“…SINEs (e.g. Alu repeats) and other transposed sequences are known to serve as direct silencers of gene expression due to their repressed chromatin marks (histone H3 methylated at Lys9) [72][73][74] . Moreover, some non-B DNA structures including G4, cruciform, triplex and Z-DNA have been shown to potently silence expression of adjacent genes [75][76][77][78][79][80][81][82][83][84][85] .…”
Section: Discussionmentioning
confidence: 99%